1997
DOI: 10.1038/nsb0997-699
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of RhoA–GDP and its functional implications

Abstract: RhoA, a ubiquitous intracellular GTPase, mediates cytoskeletal responses to extracellular signals. A 2.1 A resolution crystal structure of the human RhoA-GDP complex shows unique stereochemistry in the switch I region, which results in a novel mode of Mg2+ binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
141
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(150 citation statements)
references
References 30 publications
5
141
0
4
Order By: Relevance
“…In that study, the authors point out the unusual feature of the solvent exposed lipophilic amino (29). Switch I undergoes conformational changes during nucleotide exchange but the solvent accessibility of the side chain of Asn 41 does not change, as can be deduced from the crystal structures of Rho-GTP and Rho-GDP (27,30). The nucleotide-dependent time course of the ADP-ribosylation revealed that Rho-GDP is the optimal substrate and that binding of the GTP analogues Gpp(NH)p or GTP␥S decreases the rate of reaction by a factor of five but does not change the total amount of ADP-ribosylation.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the authors point out the unusual feature of the solvent exposed lipophilic amino (29). Switch I undergoes conformational changes during nucleotide exchange but the solvent accessibility of the side chain of Asn 41 does not change, as can be deduced from the crystal structures of Rho-GTP and Rho-GDP (27,30). The nucleotide-dependent time course of the ADP-ribosylation revealed that Rho-GDP is the optimal substrate and that binding of the GTP analogues Gpp(NH)p or GTP␥S decreases the rate of reaction by a factor of five but does not change the total amount of ADP-ribosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Only the use of a dominant negative RhoA or inactivation of Rho by C3 exoenzyme could induce apoptosis in our studies. The switch 1 mutant RhoA A37 is likely functioning as a dominant negative in our studies because it cannot stabilize Mg 2+ chelation in its GTPbound form, thus favoring the GDP-bound inactive form (Wei et al, 1997). This might permit sequestration of Rho guanine nucleotide exchange factors from interacting with endogenous Rho protein.…”
Section: Discussionmentioning
confidence: 99%
“…GS is composed of a catalytic subunit encoded by the two homologous genes FKS1 and FKS2 (Inoue et al, 1995;Mazur et al, 1995), and a regulatory subunit, the small GTPase, Rho1p (Drgonova et al, 1996;Qadota et al, 1996). The Rho-type GTPase is generally regulated by switching between a GDPbound inactive state and a GTP-bound active state (Wei et al, 1997;Ihara et al, 1998). Various factors are involved in the regulation of ␤-1,3-glucan synthesis by Rho1p in yeast cells.…”
Section: Discussionmentioning
confidence: 99%